Communication training at undergraduate level. An analysis of health and life sciences, environmental sciences and natural sciences - Revuelta, Gema (InMediaciones de la Comunicación, 2018)
The aim of this research is to analyze the communication training received by under-graduate students from the areas of health and life sciences, environmen tal sciences and natural sciences. For this purpose, the whole of the Spanish university system (84 universities) and a sample of 10 universities belonging to six Latin- American countries have been studied. Starting from a documentary analysis of their websites, 91 courses were identified that gather the inclusion criteria: 48 in the medical degree, 18 in life sciences (biomedicine and biotechnology, mainly), 13 in environmental sciences and other natural sciences and 12 in other health sciences (such as psychology, nursing, nutrition pharmacy, gerontology, neuroscience or veterinary science). As well, a content analysis of the teaching programs of these courses has identified seven main thematic categories. These seven categories are: 1) theories of communication and communication-based interventions; 2) communication in action: actors, interpersonal relationships and communication environments; 3) nature of science and specific elements of the disciplinary field; 4) communication in mass media and its social impact; 5) ethical aspects of communication; 6) general communication skills and techniques; and 7) special situations skills.